Peran Ganda Wanita Karir dalam Hadis (Sebuah Tinjauan Psikologi) - Sundari Sundari (Jurnal Riset Agama, 2022)
This research aims to discuss the hadiths regarding the dual role of career women with psychological theory. This research applies qualitative types through literature studies using takhrij methods and hadith sharah. The results and discussion of this study include an overview of the dual role of women's careers, the redaction of hadiths on the dual role of career women, the concept of hadith in addressing the role of doubles among career women with psychological theory. The study concluded that women who go out to work psychologically arise from within themselves as a form of self-actualization as well as a hadith context that does not prohibit women from leaving the house to work. This research has limitations especially in psychological review, so researchers recommend that further research be conducted with the collaboration of researchers across disciplines discussed in the research theme.